Tindak Pidana Pemalsuan Ijazah Dalam Perspektif Hukum Pidana Indonesia - Muhammad Jarnawansyah (CV. Aksara Global Akademia, 2025)
Forgery of diplomas constitutes a criminal act that undermines the integrity of the national education system and negatively impacts public trust in educational institutions as well as law enforcement in Indonesia. This study aims to thoroughly examine the criminal law regulations governing diploma forgery, particularly under Article 263 of the Indonesian Criminal Code (KUHP), along with the essential elements required for an act to be classified as diploma forgery. Furthermore, the study explores the implementation of criminal law in handling diploma forgery cases in Indonesia, including the challenges and obstacles faced by law enforcement officers and the structural and cultural factors affecting the effectiveness of law enforcement. This research employs a normative legal approach, utilizing statutory, conceptual, and case study methods to obtain comprehensive theoretical and empirical insights. The findings reveal that despite the existence of clear and stringent legal provisions, law enforcement practices still encounter barriers such as inadequate diploma verification systems, the absence of an integrated national diploma database, and low public legal awareness regarding the consequences of diploma forgery. Cases involving professional individuals committing diploma forgery underscore the need for more consistent and systematic law enforcement. Consequently, this study recommends the development of an integrated national diploma database, enhancement of law enforcement capacity and coordination, intensified public legal education and outreach, and the strict application of legal sanctions to effectively prevent and prosecute perpetrators of diploma forgery